Effects of copulation and male size on the oviposition behavior of the manure fly Archisepsis diversiformis (Diptera: Sepsidae). - Baena Hurtado, Martha Lucía (2009)
I evaluated the effect of copulation as a stimulation factor for oviposition of Archisepsis diversiformis by using two different age groups of females. In addition, I tested the effect of copulation on female longevity and progeny sex ratio, taking into account female and male size, and oocyte development in relation to female age. A delay in copulation leads to a delay in oviposition. Females of both age groups started to oviposit between four and five days after copulation. The number of eggs that were laid during the first ten days after copulation, the average number of ovipositions (number of eggs laid per day) during the female’s life, and the average time between ovipositions were all similar. I found further evidence for the effect of copulation on oviposition: when females copulate, they oviposited faster than virgin females. In addition, these females laid a lower number of eggs after the age of 13 days, while females of the same age (that have copulated before, when they were two or six days old) laid a higher number of eggs (an average of 75 eggs). Oocytes in virgin females became larger with age; 57 % of the variation in the number of eggs laid by females depends on female’s longevity. As in other studies, female size had an effect on the total number of eggs laid. However, male size significantly affected the oviposition rate (total number of eggs/female longevity). Females tended to have a higher oviposition rate after copulating with larger males. These data suggest that for this fly species, sexual selection through female choice might be occurring